Green information technology (Green IT) perspectives, motives, barriers, and solutions within manufacturing companies - AbuAlRejal, Hussein; Mohamed Udin, Zulkifli (2012)
There is still little common understanding of what green IT actually means, the measure to determine the capability of organizations to Green their IT remains elusive.In Malaysia Green IT development is still at the early stage, greater efforts and promotion is required to ensure understanding and success of development and implementation of Green Technology Policy in Malaysia.To overcome some of misunderstanding in Green IT field, this paper clarifies deferent perspectives and some important related issues like motives, readiness, barriers, and solutions within green IT paradigm. The researchers have reviewed previous literatures to ensure wide understanding for issues regarding green IT.